2014
DOI: 10.1149/2.0571414jes
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transport Property in Supported Nafion Nanothin Films by Electrochemical Impedance Spectroscopy

Abstract: The proton transport property of Nafion nanothin films (4-300 nm) has been investigated by electrochemical impedance spectroscopy (EIS) using interdigitated array (IDA) of gold electrodes on SiO 2 substrate. The proton conductivity has been investigated as a function of film drying/heating protocol, relative humidity, temperature and film thickness. It is found that the film treatment protocol makes a difference in film transport property. Ultimately, the proton conductivity and capacitance of the Nafion nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
206
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(240 citation statements)
references
References 47 publications
19
206
3
1
Order By: Relevance
“…Moreover, with increasing current density, HFR distribution becomes less nonuniform and overall HFR does not vary much between 0.2 V and 0.1 V. Along with the dehydration of membrane the ionomer dehydration in catalyst layer also accounts for the significant ohmic voltage loss because proton conductivity of few nanometer thick ionomer film is much lower than the conductivity of bulk membrane, especially in dry condition. 33 In Figure 6c, at 60% RH the local current generation is uniform for all the segments at cell voltages above 0.4 V, corresponding to overall current density lower than 1.3 A/cm 2 . However there is variation in HFR to a certain extent.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, with increasing current density, HFR distribution becomes less nonuniform and overall HFR does not vary much between 0.2 V and 0.1 V. Along with the dehydration of membrane the ionomer dehydration in catalyst layer also accounts for the significant ohmic voltage loss because proton conductivity of few nanometer thick ionomer film is much lower than the conductivity of bulk membrane, especially in dry condition. 33 In Figure 6c, at 60% RH the local current generation is uniform for all the segments at cell voltages above 0.4 V, corresponding to overall current density lower than 1.3 A/cm 2 . However there is variation in HFR to a certain extent.…”
Section: Resultsmentioning
confidence: 90%
“…• C and relative humidity below 95% RH, Paul et al 33 measured conductivity of ionomer film of 4 nm thickness (typical ionomer film thickness in catalyst layer) and found that the conductivity much less than bulk membrane. In our work the cell is operated in the similar conditions as that of Neyerlin et al 32 so that the equations are useful to determine local oxygen reduction overpotential.…”
mentioning
confidence: 99%
“…60 Despite the small difference in activation energy, the conduction mechanism in the case of nanocellulose is likely to be dominated by a Grotthuss-like, water mediated mechanism. [61][62][63] At lower humidity levels the vehicle mechanism dominates proton conduction. Here, protons diffuse as H 3 O + hydronium ions whilst a counter diffusion of unprotonated water occurs.…”
Section: Porementioning
confidence: 99%
“…The value of 0.36 S cm −1 is impressively high and exceeds the proton conductivity of a commercial Nafion@211 membrane (0.13 S cm −1 at 353 K and 95% RH) by a factor of almost 3. It should be noted that the reported NAFION nanofilm with a thickness of 300 nm yields comparable conductivities to that of Nafion membrane . We attribute the very high proton conductivity of the SURGELs to the regular packing of proton hopping sites.…”
Section: Resultsmentioning
confidence: 63%